The Europeanisation of Cyprus’ Foreign Policy and its effect on its bilateral relations with Russia. - Vasileiou, Florentia; Huntley, Matthew David; Kočí, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The Republic of Cyprus has maintained a neutral foreign policy since its establishment in 1960, aiming to maintain good relations with a wide range of nations, one of those being the Russian Federation. After it acceded to the European Union in 2004, it strived to Europeanise itself and reflect its newfound status. For the past 10 years, the relationship between the EU and Russia deteriorated, yet Cyprus maintained its friendship with the nation. This study aims to examine whether Cyprus’ foreign policy has changed after it acceded to the EU, specifically regarding its bilateral relations with Russia. To examine whether their bilateral relations have been affected by the accession, discourse analysis of EU FP guidelines on Russia and the subsequent reactions of Cyprus, an overview of the recent Citizenship by Investment (CBI) programme and a small-scale qualitative survey are used. All three sections are analysed through the scope of Europeanisation theory and constructivism. The results showed that, due to the identity construction the two states have for each other, their bilateral relations have not been affected by Cyprus’ accession to the EU. However, some elements of Europeanisation are present in its approach to its national FP, in this case when discussing the Cyprus problem or during the scandal over the CBI programme. Moreover, the survey provided an insight into the opinions and constructions of identities that Cypriot students have for CY-RU and CY-EU relations. However, due to the limited number of participants, larger-scale research on several age groups is necessary to further contribute to this topic.
Vedoucí práce: Matthew David Huntley
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses